3-D analysis of dictyosomes and multivesicular bodies in the green alga Micrasterias denticulata by FIB/SEM tomography() - Wanner, Gerhard (Academic Press, 2013)
In the present study we employ FIB/SEM tomography for analyzing 3-D architecture of dictyosomes and formation of multivesicular bodies (MVB) in high pressure frozen and cryo-substituted interphase cells of the green algal model system Micrasterias denticulata. The ability of FIB/SEM of milling very thin ‘slices’ (5–10 nm), viewing the block face and of capturing cytoplasmic volumes of several hundred μm(3) provides new insight into the close spatial connection of the ER–Golgi machinery in an algal cell particularly in z-direction, complementary to informations obtained by TEM serial sectioning or electron tomography. Our FIB/SEM series and 3-D reconstructions show that interphase dictyosomes of Micrasterias are not only closely associated to an ER system at their cis-side which is common in various plant cells, but are surrounded by a huge “trans-ER” sheath leading to an almost complete enwrapping of dictyosomes by the ER. This is particularly interesting as the presence of a trans-dictyosomal ER system is well known from mammalian secretory cells but not from cells of higher plants to which the alga Micrasterias is closely related. In contrast to findings in plant storage tissue indicating that MVBs originate from the trans-Golgi network or its derivatives our investigations show that MVBs in Micrasterias are in direct spatial contact with both, trans-Golgi cisternae and the trans-ER sheath which provides evidence that both endomembrane compartments are involved in their formation.